Pengaruh APIP, BPK, dan DPRD dalam Penegakan Tata Kelola Pemerintahan Daerah yang Baik (Good Government Governance) dengan Pengendalian Internal sebagai Variabel Moderasi (Studi Empiris pada Provinsi Riau) - Novira Fazri Nanda; Muhammad Rasuli; Taufeni Taufik (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
Good governance is indeed highly demanded at this time. Where today there are rampant cases of corruption, collusion and nepotism. For this reason, both the regional government and the central government are required to create good governance. To achieve good governance that needs to be considered is supervision, control and enforcement. For this reason, a role is needed from APIP, BPK, and DPRD. The governance of Riau Province is included in the category of good tendencies. Nevertheless there are still a number of arenas which have less value, especially in the government arena. For this reason, this study will look at the influence of APIP, BPK, DPRD in enforcing good governance (GGG) with internal control as a moderating variable in Riau Province. The results of this study indicate that APIP, BPK and DPRD have a significant influence on the enforcement of good governance. And internal control strengthens the role of APIP, BPK, and DPRD in upholding good governance.